Digest: Biased male–male competition drives asymmetric introgression in lizards. (1st October 2020) - Wielstra, Ben
Abstract: Introgression, gene flow from one population into another, can be asymmetric. Yang et al. suggest that reduction of gene flow in one direction, rather than elevated gene flow in the opposite direction, explains the pattern of asymmetric introgression between two lizard lineages. The authors propose that a dominant male phenotype in one lineage blocks a submissive male phenotype from another lineage in mating with females of the opposite lineage. This case underscores just how capricious introgression can be.